The Value of the Vestibular/Ocular Motor Screening (VOMS) in Evaluating Adolescent Patients with Concussions - Laura Harris; Kirstin Antonaros; Hayley Cole; Patrick Daniels; Kurtis Gould; Trent Ivey; Alexa Lewis; Alexis Maxwell; Paul Miles (Bowling Green State University, 2023)
To determine the VOMS can differentiate between typical and protracted recoveries in adolescent patients.